The impact of climate change on land degradation along with shoreline migration in Ghoramara Island, India. (June 2022) - Halder, Bijay; Ameen, Ameen Mohammed Salih; Bandyopadhyay, Jatisankar; Khedher, Khaled Mohamed; Yaseen, Zaher Mundher
Abstract: Sea level rise (SLR) due to climate change is affecting the coastline, causing shoreline changes, the degradation of mangrove forests, and the destruction of coastal resources. This is the cause of a huge amount of mangrove degradation in many parts of the Ganges–Brahmaputra–Meghna delta. A total of 90% of people have been forced to migrate from the island due to extreme weather conditions. In this study, remote sensing (RS) and geographic information system (GIS) techniques were used for LULC change and shoreline shift analyses of Ghoramara Island. LULC classification was carried out using thirty years of Landsat datasets with intervals of ten years (1990 and 2000) and intervals of five years (2005, 2010, 2015, and 2020). The classification was conducted using a supervised classification method. The field survey data were used to validate the classification results. The total area was reduced from 608 ha (in 1990) to 375 ha (in 2020) due to the extreme weather conditions. Around 39% of the land area was found to be degraded due to shoreline changes. The LULC classes of built-up area, agricultural land, water bodies, and vegetation were found to have lost around 62.345 ha, 63.328 ha, 0.836 ha, and 113.241 ha, respectively, from the year 1990–2020. It was observed that the shoreline shifted towards the north-east, north-west, and southern directions in the last thirty years. This study identified the land use changes due to shoreline shifting and proposed the appropriate to achieve the sustainable development of Ghoramara Island. Highlights: ➢ Remote sensing and GIS techniques are used for LULC change and shoreline shift ➢ A case study of Ghoramara Island is selected as for this investigation ➢ LULC classifications are conducted using thirty years of Landsat datasets (1990–2020) ➢ Ghoramara Island lost around 39% of the land between the years of 1990–2020 ➢ The Shoreline shifted towards north-east, north-west and southern direction